Short-term repeat HPV testing for triaging HPV-positive women in cervical cancer screening - Armando Baena; Marı́a Alejandra Picconi; Laura Mendoza; Annabelle Ferrera; David Mesher; Johana Lineros; Marisol Brizuela; Pamela Mongelós; Yessy Cabrera; Marı́a Dolores Fellner; Osmalia Zambrana; Laura García; et al. (My University, 2025)
BACKGROUND: Persistent HPV infection causes cervical cancer, but most infections are transient. Triage methods identify high-risk women needing further evaluation or treatment. We assessed short-term repeat HPV testing as an alternative triage option. METHODS: In ESTAMPA, women aged 30-64 years were screened with HPV testing (HC2 or Cobas) and cytology. Screen positives were referred to colposcopy approximately two months after screening, where cervical samples were collected again for repeat HPV testing. We evaluated the performance of repeat HPV for CIN3+ among HPV-positive women and explored its combination with limited HPV genotyping (HPV16/18). RESULTS: Among 5390 HPV-positive women (including 629 CIN3 cases and 53 cancers), 61% retested positive at ~2 months (median: 1.8, interquartile range: 1.2-2.8). Repeat HPV sensitivity for CIN3+ was 81.5% (95% CI 77.2-85.2) for HC2 and 87.7% (83.7-90.8) for Cobas. Specificity was <50% with referral rates of 57.4% (55.7-59.0) and 68.2% (66.1-70.2) for HC2 and Cobas. HPV16/18 genotyping followed by repeat HPV among non-HPV16/18-positive women did not greatly improve performance. However, HPV16/18 positivity doubled the risk of CIN3+, supporting its combination with repeat HPV when available. CONCLUSIONS: Short-term repeat HPV testing could be a practical option for triaging HPV-positive women, either alone or in combination with limited HPV genotyping. TRIAL REGISTRATION: ClinicalTrials.gov, NCT01881659.
Keywords: Medicine; Cervical cancer screening; Cervical cancer; Gynecology; Oncology; Cervical screening; Medical screening; Internal medicine; Human papillomavirus; Papillomaviridae; Cancer screening; MEDLINE; Colposcopy; Uterine cervix; Predictive value of tests; Retrospective cohort study; Epidemiology; Obstetrics; Cancer; Cervix; Risk assessment; Premalignant lesion; Screening test; Sexually transmitted disease; Cervical intraepithelial neoplasia; Young adult; Cervical carcinoma; Viral disease; Cervical cancer screening; Cervical cancer; Cervical screening; Medical screening; Human papillomavirus; Papillomaviridae; Cancer screening; MEDLINE; Colposcopy; Adult; Adult; Adult; Adult; Uterine Cervical Dysplasia diagnosis; Uterine Cervical Dysplasia diagnosis; Uterine Cervical Dysplasia diagnosis; Uterine Cervical Dysplasia diagnosis; Uterine Cervical Dysplasia virology; Uterine Cervical Dysplasia virology; Uterine Cervical Dysplasia virology; Uterine Cervical Dysplasia virology; Uterine Cervical Neoplasms diagnosis; Uterine Cervical Neoplasms diagnosis; Uterine Cervical Neoplasms diagnosis; Uterine Cervical Neoplasms diagnosis; Uterine Cervical Neoplasms pathology; Uterine Cervical Neoplasms pathology; Uterine Cervical Neoplasms pathology; Uterine Cervical Neoplasms pathology; Uterine Cervical Neoplasms virology; Uterine Cervical Neoplasms virology; Uterine Cervical Neoplasms virology; Uterine Cervical Neoplasms virology; Colposcopy; Colposcopy; Colposcopy; Colposcopy; Female; Female; Female; Female; Genotype; Genotype; Genotype; Genotype; Humans; Humans; Humans; Humans; Middle Aged; Middle Aged; Middle Aged; Middle Aged; Triage methods; Triage methods; Triage methods; Triage methods; Papillomaviridae genetics; Papillomaviridae genetics; Papillomaviridae genetics; Papillomaviridae genetics; Papillomaviridae isolation & purification; Papillomaviridae isolation & purification; Papillomaviridae isolation & purification; Papillomaviridae isolation & purification; Papillomavirus Infections diagnosis; Papillomavirus Infections diagnosis; Papillomavirus Infections diagnosis; Papillomavirus Infections diagnosis; Papillomavirus Infections virology; Papillomavirus Infections virology; Papillomavirus Infections virology